MEMBANGUN CONTENT MANAGEMENT SYSTEM (CMS) UNTUK PENGATURAN BERITA ON LINE DENGAN MENGEMBANGKAN FITUR NEWS PUBLISHING - Dwi Retnoningsih (Universitas Sahid Surakarta, 2010)
Many features included in the CMS (Content Management System) such as Joomla, Mambo and others, make the beginner users who have not familiar about the web design tends to have difficulty in managing the CMS-based website The purpose of this research is to build a CMS for the purposes of setting the news on line with the developing news publishing features. Therefore expected to provide convenience to the user in making the news portal and allows administrators to manage the website. Research methods used in this study is the observation, interviews, literature studies, and experiments. This research produced a new CMS that provides convenience to the users to manage and make dynamic content changes, especially for setting the news on line. The ability of this CMS for example are: have an easiness in build interface or its programming, because almost all the commands using Indonesian. Has facilities in management compared with the existing CMS today, because the facilities provided in a simple designed to be easily understood by users and web programmers